Gambaran Penangguhan Pendonor di Unit Donor Darah PMI Kota Yogyakarta Tahun 2022 - Armayanti, Denisa; Purnamaningsih, Nur'Aini; Astuti, Yuli (Jurnal Sehat Mandiri, 2023)
In blood donors,donor defferal are often encountered,namely donors who are temporarily or permanently refused to donate blood. The reasons for refusing to donate blood need to be studied further to find out the causative factors.This study aims to determine the causes of the temporary defferal of donors at the PMI Yogyakarta Blood Donor Unit in 2022.This research is a quantitative descriptive study,with a retrospective approach.The population of this study is all donors defferal at the PMI Blood Donor Unit in Yogyakarta City in 2022.with a total sampling technique obtained a sample of 7.677 deffered donors.Of the 42,685 donors,7,677(17,9%)deffered donors,while 35,008(82,1%)passed. Donor deffered based on body weight found <50 kg in 76 people(1,0%),low blood pressure in 1,260 people(16,4%),high blood pressure in 1,247 people (16,2%),low hemoglobin level in 2,380 people(31,0%),high hemoglobin level in 1,802 people(23,5%),vaccination in 139 people (1,8%),flu in 55 people(0,7%),cough in 407 people(5,3%),38 people(0,5%)had travel history,273 people(3,6%)took medication,no tattoos,piercings,and infectious diseases were found.The majority of donor deffered at Blood Donation Unit PMI Yogyakarta City in 2022 are mostly due to low hemoglobin levels(31,0%).The conclusion of this study is that the majority of donor defferal at the PMI Blood Donor Unit in Yogyakarta City in 2022 are mostly due to low hemoglobin levels.Suggestions for the Blood Donor Unit to be able to educate the public about blood donation and efforts to maintain health for donors can pass donor selection.